Algorithmic tyranny and artificial intelligence totalitarianism in digital society: A critical perspective - Tomi Setiawan; Jayum Anak Jawan; Shifwah Murran Nashifa (JURNAL ILMU SOSIAL, 2025)
The dominance of algorithms in the social, economic, and political life of the 21st century has created unprecedented structural dependencies, with complex socio-political implications. This research aims to uncover the mechanisms of algorithmic tyranny in social governance, analyze the transformation of AI into a totalitarian tool, and formulate a democratic oversight framework based on cross-national empirical findings. The study uses a critical-realist paradigm with post-qualitative methods, combining reverse engineering of controversial AI systems with critical analysis of over 40 reputable journals and books, and 14 policy documents (2015–2025). A rhizomatic analysis approach is used to explore the multidimensional nature of algorithmic power beyond hierarchical structures. Validity was established through catalytic validity to ensure epistemological and social impact. The research findings reveal regulatory differences across countries: the European Union leads in transparency but hinders innovation, while the US dominates with risks of fragmentation and minimal accountability. China uses AI for social control, and Singapore adopts a pro-business hybrid model. Algorithmic tyranny emerges in recommendation systems that create filter bubbles while judicial algorithms exhibit racial bias. Additionally, there is a totalitarian threat in the use of AI for mass surveillance and political deepfakes, meeting the criteria for “totalitarianism 2.0”. This study concludes with a novelty emancipatory concept to challenge algorithmic tyranny, through the instruments of an ”Algorithm Constitutionalism” and a ”Right to Algorithmic Explanation”. The policy recommendations emphasize the need for a global alliance to balance innovation with the protection of human rights in the algorithmic realm.